Breaking the Wall of Indigenous and Scientific Knowledge - Obanda, Johanssen (My University, 2020)
Over centuries, indigenous communities have managed to withstand epidemics, climate crises and ecosystem erosions and live on their territories sustainably by closely observing and managing well the limited natural resources they depend on. These proven indigenous knowledge systems have been - and continue to be - facing suppression, belittling and exploitation throughout and after colonialism. In my community today around Lake Victoria, indigenous knowledge suffers isolation and extinction as the continent experiences technological advancements for the price of ecosystem destruction. Furthermore, building synergies between indigenous knowledge and modern science is still a challenge. The Turkana, Maasai, Samburu and other indigenous groups in Kenya rely on their community knowledge acquired and accumulated over centuries, covering indigenous concepts about astronomy, physics, medicine, botany, zoology, psychiatry, and non-invasive technology. However, their rich knowledge base is being faced by extinction as the older generations are losing more and more opportunities of passing their knowledge on. Most indigenous languages are only spoken, hence knowledge capture is difficult. I want to build a bridge between indigenous and academic knowledge systems. This will be achieved through a series of events to facilitate meetings between indigenous community representatives and local researchers to explore opportunities for collaboration utilizing the infrastructure and network created through my work with Pint of Science Kenya. The event series will have its peak with a sustainable science communication festival under the theme of “Nature for Life, Life for Nature” showcasing indigenous music, science and art and presenting the initiated collaborative activities and research projects while ensuring protection from misappropriation. The process will be paralleled by the fostering of equitable engagement of both indigenous knowledge holders and scholarly scientists through communication and collaboration, aided by documentation and archiving in audio/visual files of interviews, video footage and scholarly documentation as with books, manuscripts and journal articles in the pan-African repository AfricArXiv. Modern Science and Indigenous Science can not only co-exist but instead complement each other to allow us to tackle continental and global challenges like climate change, the pandemic, forced migration and poverty. I believe that Indigenous Knowledge deserves an equal position alongside mainstream academic science. I am convinced that the global research community benefits from a balanced exchange of knowledge and experience from all parts of the world, especially as we address global challenges.
Keywords: Indigenous Knowledge; Science Communication; Kenya